Development and Assessment of a Hybrid Solar-Based Multi-Generation System for UAE - Ahmed, Mohamed Khaled (2020)
A Master of Science thesis in Mechanical Engineering by Mohamed Khaled Ahmed entitled, “Development and Assessment of a Hybrid Solar-Based Multi-Generation System for UAE”, submitted in July 2020. Thesis advisor is Mohamed Gadalla. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form)